1991
DOI: 10.1002/ajhb.1310030205
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of recalled estimates of menarcheal age in a sample of older women

Abstract: The accuracy of recalled age at first menses has been questioned, particularly if subjects are relatively old. This paper illustrates the use of a statistical technique that quantifies the reliability of recalled age at menarche based on re-interview of a small (15-20) subsample of subjects. Menarcheal age collected with the retrospective method in a sample of 108 females, 50 years of age and older, from Limón, Costa Rica, is reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Goodman et al (1984) found a high degree of concordance (90%) between subjects' reported ages at menarche and perceptions of such ages as early, average, or late. Damon et al (1969) and Roberts et al (1986) concluded that mean age at menarche obtained with either technique is not significantly different (Bean et al, 1979;Madrigal, 1991). Furthermore, several studies yielded a reliability of 75-90% for the retrospective method (Livson and McNeill, 1962;Damon et al, 1969;Damon and Bajema, 1974;Bean et al, 1979) and concluded that the correlation between observed age at menarche and reported ages at menarche is sufficiently high for the recalled menarcheal age to be considered accurate.…”
Section: Age At Menarchementioning
confidence: 88%
“…Goodman et al (1984) found a high degree of concordance (90%) between subjects' reported ages at menarche and perceptions of such ages as early, average, or late. Damon et al (1969) and Roberts et al (1986) concluded that mean age at menarche obtained with either technique is not significantly different (Bean et al, 1979;Madrigal, 1991). Furthermore, several studies yielded a reliability of 75-90% for the retrospective method (Livson and McNeill, 1962;Damon et al, 1969;Damon and Bajema, 1974;Bean et al, 1979) and concluded that the correlation between observed age at menarche and reported ages at menarche is sufficiently high for the recalled menarcheal age to be considered accurate.…”
Section: Age At Menarchementioning
confidence: 88%
“…In addition, age at menarche was asked retrospectively and therefore it may not be exact. It has, however, been shown that women remember quite well their first menstrual bleeding [27,28]. The subjects have possibly had other health problems in adolescence, such as eating disorders, which might have led to late menarche and might confound this relationship.…”
Section: Discussionmentioning
confidence: 92%
“…However, it may well be that the difference of 0.6 (province of Rome) and 0.4 years (Molise) obtained in the present series may diminish with an increase in sample size in view of a difference of only 0.3 years reported by Wellens et al (1990) for 4,894 Flemish girls. However, as outlined by Madrigal (1991), ultimate evaluation of reliability of recalled age at first menses may be obtained only by repetition of interviews of the same subjects after a time interval -9 months, a procedure not possible in our case.…”
Section: Discussionmentioning
confidence: 94%